STUDENTS FROM KEELE UNIVERSITY U.K. PLEASED WITH VALUABLE EXPERIENCE GAINED AT USM AND MALAYSIA - MPRC, Pusat Media & Perhubungan Awam (USM, 2015)
PENANG, 4 August 2015 – Universiti Sains Malaysia (USM) is hosting six undergraduate and masters’ students from the University of Keele, U.K under a collaboration between USM and Keele which began seven years ago.